Artificial intelligence and integrated intelligent information systems emerging technologies and applications - Zha, Xuan F. 1965- (Gale virtual reference library, 2007)
"This book presents the recent advances in multi-mobile agent systems, the product development process, fuzzy logic systems, neural networks and ambient intelligent environments among many other innovations in this exciting field"--Provided by publisher.